Evolución probatoria con finalidad de sostenibilidad procesal: Un enfoque a partir de las redes sociales y la virtualidad. (Revista Escenarios Sociojurídicos, 2023)
The sustainable development goals, also known as the 2030 Agenda, in which a large series of goals and indicators are grouped that seek to guide global efforts to achieve sustainable development in all social, economic and environmental aspects, within the which we can observe the Sustainable Development Goal number 16, "Peace, Justice and Strong Institutions", established by the United Nations, represents a global commitment to promote peace, guarantee justice and strengthen institutions throughout the world. Thus, this objective seeks to guarantee equal access to justice for all, promoting transparent, efficient and inclusive judicial systems. Therefore, being an inclusive system, it allows any procedural action that is being carried out to be carried out in person and virtually, that is, through these two modalities, the assessment of the evidence must provide certainty. to all parties, that is, by means of parameters that must establish the reality that this modality of virtuality brings with it in the request, in the decree, the practice and the evaluation of the evidence, in addition to being taken into account as elements probative materials that can be extracted from social networks, which meet the necessary requirements of relevance, conduct and need for it. Consequently, adjusting the judicial system to the guidelines established from the perspective of globalization and its commitment to more sustainable societies, the intelligent application of technology is given, in harmony with the changing legislation that allows building a future where humanity and the sustainability are intertwined in a promising dance in which a symbiosis of virtual judicial proceedings is generated, where it is possible to cover aspects such as electronic communication between the procedural subjects, the presentation of writings, evidence and the holding of virtual hearings, among others.